Post-2008 Fiscal Stimulus Packages and the Driving Forces for China’s Urbanization - David W. H. Wong; Harry F. Lee; Simon X. B. Zhao; Andy C. L. Tai (Land, 2022)
A growing body of research has sought to determine how different factors have affected urbanization in developed countries over the past decades. Yet, few studies have systematically examined urbanization’s driving forces, particularly in emerging economies. In 2008–2009, the Chinese government announced an economic stimulus program to revitalize an economy struck by the 2007–2008 Global Financial Crisis. This study aims to identify how urbanization’s driving forces evolved under a drastic change in fiscal policy and revisit the conventional urbanization theories in the Chinese context. Using a dataset covering 31 Chinese provinces and spanning the periods 2005–2011 and 2013–2015, we employ panel data regressions to analyze whether such a fiscal arrangement affected urbanization in China. Throughout the entire period, the fiscal stimulus program caused a change in the drivers for urbanization at the national and regional levels. Before the implementation of the program, industrialization drove urbanization. After the program’s implementation, land financialization was crucial in promoting urbanization across the country. Our findings challenge the conventional urbanization theory—industrialization is always the primary driving force of urbanization in emerging economies. Land financialization, a kind of tertiary production, can also drive urbanization significantly.